2018
DOI: 10.1186/s12958-018-0424-0
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of ART outcomes in women with different preconception TSH levels

Abstract: BackgroundTo assess whether elevated thyroid-stimulating hormone (TSH) levels before conception can predict poor outcomes of assisted reproductive technology (ART).MethodsPrior to July 2018, we searched the PubMed, EMBASE, COCHRANE, Google Scholar, and CNKI databases for studies. Retrospective or prospective reports that compared ART results in patients with subclinical hypothyroidism (SCH) with normal thyroid function were selected. Two reviewers separately reviewed each potential article for qualification, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The most commonly used commercial assays in Europe have an ULRR for serum TSH between 3.60 and 4.31 mIU/L [20]. In a recent meta-analysis, altered ART outcomes were present from TSH levels of 3.5 mIU/L and upwards, but in 2 interventional trials with LT4, an increased LBR was present only when TSH levels exceeded 4.0 and 4.5 mIU/L, respectively [13, 14, 21]. Based on these factors, therefore, we propose to define SCH (and to initiate treatment with LT4) from a TSH cutoff >4.0 mIU/L or >ULRR if the latter is >4.0 mIU/L.…”
Section: Methodology/definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly used commercial assays in Europe have an ULRR for serum TSH between 3.60 and 4.31 mIU/L [20]. In a recent meta-analysis, altered ART outcomes were present from TSH levels of 3.5 mIU/L and upwards, but in 2 interventional trials with LT4, an increased LBR was present only when TSH levels exceeded 4.0 and 4.5 mIU/L, respectively [13, 14, 21]. Based on these factors, therefore, we propose to define SCH (and to initiate treatment with LT4) from a TSH cutoff >4.0 mIU/L or >ULRR if the latter is >4.0 mIU/L.…”
Section: Methodology/definitionsmentioning
confidence: 99%
“…Furthermore, women with PCOS, POI, and idiopathic subfertility have a higher prevalence of TAI and serum TSH levels compared with fertile women [6, 9, 25]. Serum TSH levels >3.5 mIU/L are associated with impaired ART outcomes, and LT4 treatment can increase LBRs in women with TSH levels >4.0 mIU/L [11, 14].…”
Section: Screening/management In Daily Practicementioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used commercial assays in Europe have a ULRR for serum TSH between 3.60 and 4.31 mIU/L (89). In a recent meta-analysis, altered ART outcomes were present from TSH levels >3.5 mIU/L on, and based on this and the few interventional trials with LT4 that showed an increased LBR when TSH levels exceeded 4.0 and 4.5 mIU/L, respectively, guidelines propose to initiate treatment with LT4 from a TSH cutoff >4.0 mIU/L or >ULRR if the latter is >4.0 mIU/L (16,90,91,92). According to the (strict) Cochrane systemic review criteria, only one study could be included, in which 64 women were scheduled for IVF/ICSI with TSH levels >4.5 mIU/L (>80% of the women had TAI) and randomised to LT4 or no treatment.…”
Section: Thyroid Disorders and Art (Ivf/icsi) Clinical Outcomesmentioning
confidence: 99%
“…Most importantly, this study observed a higher clinical pregnancy rate when basal TSH levels were less than 2.5 mIU/L. However, whether moderately elevated TSH levels compromise ART clinical outcomes remains controversial [4][5][6][7]. Experts suggest that TSH concentrations < 2.5 mIU/L should be maintained during the ART procedure in infertile patients, especially in those with overt hypothyroidism [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%